The influence of e-referral, attitude, and subjective norm on purchase intention - Fajriyati Afdhal; Husnil Khatimah (Universitas Negeri Padang, 2023)
This study aims to analyze the extent to which the influence of e-referral, attitude, and subjective norms on purchase intention among Tokopedia consumers in Padang City. The population that will be used as research material is all consumers who have never used products at Tokopedia. The number of samples in this study was 150 respondents. Data was collected through online questionnaires and data processing was carried out through SmartPLS version 4 software. The results of this study indicate that (1) E-Referral has a positive effect on Purchase Intention (2) Attitude has a negative effect on Purchase Intention (3) Subjective Norm has a positive effect on Purchase Intention for Tokopedia Consumers in Padang City.